Under the clouds from paranoia to the digital sublime = da paranoia ao sublime digital ; - Ribas, João (Fundação de Serralves, 2015)
Since the second half of the 20th century, we have lived under the shadow of two clouds: the mushroom cloud of the atomic bomb, and the 'cloud' of distributed information networks. How did the central metaphor of cold war paranoia become the utopian metaphor of today? 'Under the Clouds' explores the contemporary sublime that has replaced the natural one, and the interrelated effects and affects of these two clouds on life and work, leisure and love, and on images, bodies, and minds. The post-war technologies of the emergent third industrial revolution have now evolved to fit in the palm of our hand; we no longer merely look at images, we now touch, scroll, pinch, and drag them. Where is the border between the self and its data shadow, between information, matter, and affect? The biological, economic, aesthetic, and political effects of living under the clouds has taken the form of new relations between data and material, as well as increasing debt and abstract financialization; the changing nature of work and sex; and new relationships between screens, images, and things. As earlier forms of technologically inflected art sought to mitigate the effects of change -- both on perception and society -- many of today's artistic practices confront the myriad interfaces and decentralized networks that continue to shape and transform daily life, forming new evolving connections between bits and atoms. -- Publisher's web site
Published on the occasion of the exhibition ... on view at the Serralves Museum of Contemporary Art from 19 June 19 - 20 September 2015
Keywords: Geschichte 1945-2015; Art, Modern / Exhibitions / 21st century; Atomkrieg; Technischer Fortschritt; Kunst; Politik; Gesellschaft; Ausstellungskatalog; Ausstellungskatalog -- Museu de Arte Contemporânea de Serralves -- 19.06.2015-20.09.2015 -- Porto